The analysis of the influence of external environment factors on the efficiency of maintenance contractors activities - Vilutiene, Tatjana; Malinauskas, Pranas (Technological and Economic Development of Economy, 2005)
The article presents the analysis of factors influencing the efficiency of dwelling maintenance contractors activities. The criteria characterizing the activities of maintenance contractors were determined performing the financial analysis of the company. The influence of external environment factors on maintenance contractors activities indicators was determined by calculating their correlation coefficients. In order to verify the calculation results the specialists from maintenance companies and heads of dwelling owners associations were interrogated. They showed the main maintenance problems and factors which influence the efficiency of maintenance process.Article in Lithuanian.Išorinės aplinkos poveikio priežiūros organizacijų veiklos efektyvumui tyrimasSantrauka. Straipsnyje pateikta daugiabučių gyvenamųjų namų priežiūros ir administravimo paslaugas teikiančių įmonių veiklos efektyvumą veikiančių veiksnių analizė. Atlikus priežiūros organizacijos finansinę analizę, nustatyti jos veiklą apibūdinantys rodikliai. Apskaičiavus rodiklių tarpusavio ryšius taikant Pearsono koreliacijos koeficientus nustatyta makroaplinkos veiksnių įtaka priežiūros organizacijos veiklos rodikliams. Apklausti priežiūros organizacijų specialistai ir daugiabučių namų savininkų bendrijų pirmininkai, kurie nurodė dažniausiai kylančias pastatų priežiūros problemas ir veiksnius, veikiančius priežiūros proceso efektyvumą.Reikšminiai žodžiai: priežiūros organizacijos, veiklos efektyvumas, aplinkos poveikis, rodiklių koreliacija.First Published Online: 21 Oct 2010